Integrated IBS Model for BIM Environment: Embodied Carbon Analysis - LEE , XIN YANG (Universiti Teknologi PETRONAS, 2020)
By observing the advancement in BIM and IBS, there are still very few to offer in integration for IBS and BIM. With the low adoption rate of IBS and BIM in Malaysia, it also indirectly creates a low rate of evaluation in respect to the sustainability of the construction projects. Conventional construction system requires long duration and complex process to conduct embodied carbon analysis but integrating BIM and Application Programming Interface (API) into embodied carbon analysis could expedite the process. Hence, it is significant to develop an API model for embodied carbon analysis within BIM environment which considers of IBS components based on CIDB standard. To accelerate the adoption rate of IBS in Malaysian, IBS catalogue was introduced by CIDB to act as a basic reference for detailing, designing, specification and capabilities of precast concrete components.